Utilization of Coconut Shell and Coir Waste into Charcoal Briquettes as an Eco-Friendly Alternative Energy - Ika Lestari Hutasuhut; Viny Volcherina Darlis; Agung Kartika Putra; Sonia Somadona; Nurul Qomar; M. Mardiansyah (Universitas Andi Djemma Palopo, 2026)
Utilizing coconut waste, particularly shells and husks, as raw material for charcoal briquettes holds great potential for supporting environmentally friendly and sustainable renewable energy. However, this waste is still not being utilized optimally, even though it can reduce environmental pollution while providing economic benefits. This study aims to evaluate the effect of varying the mixing ratio of coconut shells and husks on the physical characteristics and performance of the resulting charcoal briquettes, as well as to determine the optimal composition as an alternative energy source. The research was conducted at the Forestry Laboratory of the Faculty of Agriculture, Universitas Riau, over a five-month period (August–December 2025). The raw materials consisted of coconut shells and husks with three composition variations: 100% shells, 75% shells + 25% husks, and 50% shells + 50% husks. The carbonization process was performed conventionally for one hour. Afterward, the charcoal was ground, mixed with arpus binder, molded, and tested for briquette characteristics such as moisture content, density, and calorific value. The results showed that the 100% coconut shell briquette had the lowest moisture content (6.51%) and the highest density (0.79 g/cm³), resulting in more efficient, stable combustion and a high calorific value. Conversely, increasing the proportion of coconut husk raised the moisture content to 16.58% and lowered the density to 0.66 g/cm³, which negatively impacted briquette quality. Low moisture content and high density are key indicators of good briquette quality. In conclusion, a briquette formulation dominated by coconut shells is recommended for producing high-quality charcoal briquettes as an environmentally friendly and sustainable source of renewable energy, as well as supporting optimal coconut waste management in Riau Province and surrounding areas.